Research progress and overview of oral instant diaphragm tablets in food field - Zhao, Mingyue; Sun, Falin; Bao, Yiwen; Li, Jiaxin; Ao, Guoli; Li, Yue; Li, Bin; Shu, Chi; Si, Xu; Wang, Yuehua; Tan, Hui; Zhou, Ying; et al. (Maximum Academic Press, 2026)
Oral Dissolving Film (ODF), a new type of oral drug delivery formulation, offers advantages such as low weight, small size, convenient portability, water-free administration, and rapid dissolution in the oral cavity. It can effectively bypass the first-pass effect of the liver and enhance the bioavailability of substances. This article delves into the applications of ODF in the food field. It elaborates on the film-forming raw materials, including polysaccharides and their derivatives, non-toxic polymers, etc., and the functions of various auxiliary materials. Additionally, it introduces multiple preparation processes such as the casting method, hot-melt extrusion method, 3D printing technology, and electrostatic spinning technology, along with their advantages and disadvantages. Moreover, the measurement and evaluation indicators of ODF, such as mechanical properties, disintegration time, moisture content, pH value, encapsulation rate, oral absorption, and mucosal adhesion, are explained. Currently, ODF has been applied to foreign clinical drugs, yet there is limited research and application in the food field in China. Given its numerous advantages, ODF holds great potential for future research and application in the food industry.